THE TELEGRAM BOTT BASED LEARNING MODEL - Ahmadin Ahmadin; Evi Palenewen; Akhmad Akhmad (Program Pascasarjana Universitas Negeri Jakarta, 2021)
The objective of the study is to develop a learning media design based on Telegram Bot that can Upgrade the results of study students. Progress knowledge has brought change to the worth of education. Moment this many learning methods and models that can be used by the teacher, but fact problem is a lack of learning media no there is ingredients practice and participants educate not enough focus the in the study so which results in results study student no maximum. A subject study from a study that is Special High School students sportsman Method research used _ is method development of Research and Development (R&D). Instrument evaluation from development media earns mark eligibility 78% of expert Theory with valid category and 75.76% of media expert with category quite valid. Based on the t-test results of the results study students showed t count 38,012 > t table 2.042 and value the signification that can be obtained i.e. 0.00 < 0.05, p the showing that there are different results significant learning. _ And the N-Gain test score of 63% with category enough effective. That thing proves sufficient media usage effective for Upgrade results study student.